EXPLORING LEECH’S POLITENESS PRINCIPLE IN PLUTO (2023): A PRAGMATIC STUDY OF ANIME DIALOGUE - Dinda Aqiila Azman; Mhd Syafiq Aliy Asghar; Olyvia Basariah P M Purba; Kristina Cut Noprilita Samosir (Fakultas Sastra UMN AL Washliyah, 2026)
This study investigates politeness strategies in the anime series Pluto (2023), adapted from Naoki Urasawa’s reimagining of Tezuka’s Astro Boy. Grounded primarily in Leech’s (1983) Politeness Principle. The data were selected dialogue excerpts that explicitly reflected interpersonal negotiation, which were collected through documentary and note-taking techniques. Following Miles, Huberman, and Saldaña’s (2014) interactive model, the analysis was conducted through data condensation, data display, and conclusion drawing. The findings reveal that the Tact and Approbation maxims are the most dominant politeness strategies, likely because these maxims reduce potential face threats and promote positive interpersonal alignment, thereby foregrounding themes of empathy, ethical responsibility, and harmonious human–robot coexistence. Instances of politeness are strategically used to mitigate conflict, assert moral positioning, and construct emotional depth in character interactions. This study contributes to media pragmatics and anime linguistics by demonstrating how Leech’s maxim-based politeness model can illuminate ethical dimensions in animated discourse and expand cross-cultural politeness inquiry beyond Japanese honorific norms.